Noname - A new quarterly model for Belgium - Philippe Jeanfils; Koen Burggraeve (National Bank of Belgium, 2005)
This paper gives an overview of the present version of the quarterly model for the Belgian economy built at the National Bank of Belgium (NBB). This model can provide quantitative input into the policy analysis and projection processes within a framework that has explicit micro-foundations and expectations. This new version is also compatible with the ESA95 national accounts. This model called Noname is relatively compact. The intertemporal optimisation problem of households and firms is subject to polynomial adjustment costs, which yields richer dynamic specifications than the more usual quadratic cost function. Other characteristics are: pricing-to-market and hence flexible mark-ups and incomplete pass-through, a CES production function with an elasticity of substitution between capital and labour below one, time-dependent wage contracting à la Dotsey, King and Wollman. Most of the equations taken individually have acceptable statistical properties and diagnostic simulations suggest that the impulse responses of the model to exogenous shocks are reasonable. Its structure allows simulations to be conducted under the assumption of rational expectations as well as under alternative expectations formations.
Keywords: C5; E2; E3; F41; 330; Econometric modelling; Pricing-to-market; CES production function; Wage bargaining; Polynomial adjustment costs; Rational expectations.; Wirtschaftsprognose; Belgien; Ökonometrisches Modell